2001
DOI: 10.1248/jhs.47.9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Fate by Cadmium and Zinc.

Abstract: Effects of the heavy metals cadmium and zinc on the regulation of cell destiny are reviewed in light of an apoptogenic metal of cadmium and the antiapoptotic nature of zinc. Exposure of renal cells to cadmium causes apoptotic features, DNA fragmentation and chromatin condensation in earlier stages of cadmium cytotoxicity than the cadmium-induced necrotic phase. The molecular mechanism of cadmium-induced apoptosis is poorly understood. Neither cadmium-metallothionein nor an immediate early gene such as c-myc is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Recent discovery of the apoptogenic nature of cadmium has revealed that metallothionein would be involved in a necrotic phase for the metal detoxification, 16,[19][20][21][22][23] whereas a putative oncogene such as Bcl-2 but not c-MYC largely attenuated cadmium toxicity in an apoptotic phase. 16,24) For further toxicological study of metallothionein using the Flagmetallothionein, a stable clone must be established since the population of the expressed fusion proteins is low in a transient expression system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent discovery of the apoptogenic nature of cadmium has revealed that metallothionein would be involved in a necrotic phase for the metal detoxification, 16,[19][20][21][22][23] whereas a putative oncogene such as Bcl-2 but not c-MYC largely attenuated cadmium toxicity in an apoptotic phase. 16,24) For further toxicological study of metallothionein using the Flagmetallothionein, a stable clone must be established since the population of the expressed fusion proteins is low in a transient expression system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the mechanisms of pollutant action are still incompletely understood. Multiple heavy metals can cause renal insufficiency and necrosis [1,2]. Although such illnesses are considered to be related to the action of proteins such as a metallothionein and to depend on the form of metal involved [2][3][4], details on the toxic mechanism are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of cells to cadmium evokes a number of responses that involve not only death-signaling reactions, but also reactions that protect the cells against toxicity (Ishido and Kunimoto, 2001). Accordingly, it has proven difficult to identify the pathways activated by the metal during cell death.…”
Section: Introductionmentioning
confidence: 99%